Erforschung Ti–Co‐basierter, bioaktiver Auftraglötschichten auf oxidischen Hochleistungskeramiken in der Medizintechnik. Issue 6 (June 2014) - Bobzin, K.; Kopp, N.; Wiesner, S.; Puidokas, S.; Samadian Anavar, S.; Fischer, H.; Korsten, A.; Schickle, K.
<x xml:space="preserve">Abstract</x> The demand of prostheses and implants made from biomaterials grows as a result of the rising age of patients. For biomaterials, such as those found in joint‐ or hip‐prostheses, that are in direct contact with the organism, not only mechanical stability is required, but also biocompatibility as well as their ability to support bone regeneration. Taking this into account, a thin‐walled bioactive titanium cobalt‐based brazing coating on high‐performance oxide ceramics (Al2O3) has been developed. Here, the coating process offers an economical and at the same time technologically simple way for the coating ceramic materials. The biocompatible coating has been enhanced by addition of bioactive particles made of bioglass and calcium phosphates in order to improve bone formation. The reactions between the bioactive particles and the brazing alloys, as well as the particular melting behavior, were determined through thermo analytical methods. The structures of the brazing alloys enriched with bioactive particles were investigated through metallographical methods. The combination of three bioactive additives and two brazing alloys were analyzed in terms of their melting behavior and the resulting porosity, the parameters of the brazing process have been gradually optimized. The results show, that the combination of calcium phosphate particles and Ti–Co alloys effectively meet the requirements for a defined porous, biocompatible brazing coating.